Nucleoside N-acylation with active derivatives of amino acids - Yarmoluk, S.M.; Kostenko, A.M.; Kryvorotenko, D.V.; Dubey, I.Y. (Биополимеры и клетка, 1996)
Simple procedure for N-acylation ofadenosine guanosine and cytidine by active derivatives of amino acids is proposed. Procedure is based on transient silyt protection ofribose hydroxy groups and consists of 3 steps: (a) silytotion of nucleoside by trimethylchloro-silane, (b) reaction of amino group ofsilylated nucleoside with chloroanhydride or active ester of N-protected amino acid, (c) desilylation of intermediate. The yields of N-amino-acylated nucleosides were about 40–90 %.